Peran Guru Dalam Meningkatkan Motivasi dan Prestasi Belajar Siswa SMP - Rotty, Viktory N. J.; Isir, Apilena; Kocu, Antoneta (Peneliti.net, 2024)
The research aims to determine the factors that support the achievement of student learning achievement in elementary schools in terms of the role of the teacher. This research was carried out at YPK 1 Imanuel Jitmau Middle School. The type of research used is descriptive qualitative research with the aim of describing the role of teachers in increasing student motivation and learning achievement at the junior high school education level. Data collection was carried out using semi-structured interviews and observation. The fundamental thing in qualitative research is the researcher as an instrument. Therefore, in research, data analysis will be carried out from the time this research takes place until data collection and the creation of a research report which is the object or target of research in the field. Qualitative data analysis is carried out in a gradual sequence of analysis activities, namely the process of data reduction, data presentation, and drawing conclusions and verifying information into statements. The research results reveal that teachers have a very important role in student motivation and achievement, such as being a demonstrator, class manager, mediator, facilitator, evaluator and motivator for students so that students can achieve their learning achievements